Sistem Pergerakan Robot Kiper Beroda Menggunakan Metode Wall Follower Berbasis Image Processing - Risfendra, Risfendra; Asfinaldi, Asfinaldi; Habibullah, Habibullah; Julisardi, Julisardi (Faculty of Engineering, Universitas Tanjungpura, 2020)
One of Indonesian Robot Contest divisions is the Indonesia wheeled soccer robot contest. There are three players called the striker, defense and goalkeeper robot, which is drived by wheels that controlled based on three aferomentioned positions. This study aims build the goalkeeper robot equipped with image processing to detect the ball using a camera sensor that installed in the the robot system. The Image processing contructed using the python programming language with OpenCV library. The results of image processing are used as input data that controlled by Arduino Mega 2560, which is connected serially to the PC's USB port. The results shows the maximum linear velocity that can be achieved is 1.59 m/s. Furthermore, the efficiency ratio of analysis data to the actual distance is 86.77 %